2021
DOI: 10.1002/path.5703
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the amniotic fluid proteome of fetuses with congenital anomalies of the kidney and urinary tract identifies plastin 3 as a protein involved in glomerular integrity

Abstract: Congenital anomalies of the kidney and the urinary tract (CAKUT) are the first cause of chronic kidney disease in childhood. Several genetic and environmental origins are associated with CAKUT, but most pathogenic pathways remain elusive. Considering the amniotic fluid (AF) composition as a proxy for fetal kidney development, we analyzed the AF proteome from non-severe CAKUT (n = 19), severe CAKUT (n = 14), and healthy control (n = 22) fetuses using LC-MS/MS. We identified 471 significant proteins that discrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…The proteins with the lowest FC values included LMAN2, ACTC1, C1QA, MYOC and VCAM1. LMAN2 encodes a type 1 transmembrane lectin that shuttles between the endoplasmic reticulum, Golgi apparatus and plasma membrane ( 21 ) and is associated with the risk of kidney function decline ( 22 ). ACTC1 encodes actin, which is involved in various types of cell motility, especially cardiac diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The proteins with the lowest FC values included LMAN2, ACTC1, C1QA, MYOC and VCAM1. LMAN2 encodes a type 1 transmembrane lectin that shuttles between the endoplasmic reticulum, Golgi apparatus and plasma membrane ( 21 ) and is associated with the risk of kidney function decline ( 22 ). ACTC1 encodes actin, which is involved in various types of cell motility, especially cardiac diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The CAKUT multi-omics data set was obtained from a previously published study and reinvestigated in collaboration with the authors of the original study 6,22 . The initial study contains amniotic fluid samples from proteome and peptidome.…”
Section: Multi-omics Data Setsmentioning
confidence: 99%
“…The peptidome and the proteome data sets were quantile normalised and log2 transformed as previously described 36,37 . Before transformation, peptide IDs were mapped to protein IDs, and were summarised into single protein-level values using geometric mean 22 . The miRNome data set was already normalised and transformed, thus the information of their target genes could be added to each miRNA ID without additional data manipulation, using the information provided by miTaRBase.…”
Section: Pathway-level Analysis To Detect Functional Linksmentioning
confidence: 99%
See 1 more Smart Citation
“…Liquid chromatography-tandem mass spectrometry (LC-MS/ MS) is a current, routine, highly accurate application in newborn screening (14,15). Similarly, metabolomics can be applied to fetal malformations by exploring the AF metabolome, and several studies have reported promising results (16,17), revealing the possibility of using this technology in clinical practice. Since AF can reflect both maternal and fetal health, linking AF metabolic profiles with structural anomalies is conducive to biomarker discovery, and will better guide clinical practice.…”
Section: Introductionmentioning
confidence: 99%